Exploring Healthcare Paradoxes in Hospital Haemodialysis-A Qualitative Study - Tone Andersen‐Hollekim; Torstein Hole; Marit Solbjør (Wiley, 2024)
ABSTRACT Introduction The complex logics of healthcare systems inherit paradoxes that can lead to interpersonal conflicts impacting both patients and professionals. In this study, we aimed to identify and explore tensions and conflicts arising from paradoxes within hospital haemodialysis. Methods We conducted a secondary supplementary analysis to previously collected qualitative data, including individual interviews with 11 patients and 10 nephrologists and focus groups involving a total of 13 haemodialysis nurses. Data were collected in Norway through three primary studies focused on exploring experiences of patient participation. For the current study, we employed thematic analysis. Results Patient-professional conflicts emerged in three fundamental areas: (1) the hospital haemodialysis treatment, in which patients' views of treatment diverged from those of professionals, (2) patient-professional responsibility that became a negotiation point, with differing views on responsibilities, and (3) time, in which professional time took precedence over patients' time, indirectly impacting patients due to resource allocation. These conflicts stemmed from paradoxes driven by unevenly validated principles, conflict of interest, and conceptual ambiguity. Conclusion Altering healthcare logics by bringing in new perspectives or clarifying conceptual ambiguity could mitigate patient-professional conflicts. However, changing existing healthcare logics may give rise to new paradoxes and conflicts, which health services at various levels must address. Patient or Public Contribution This secondary analysis utilized previously collected data from a project that did not involve patient or public contribution.